Response of macroinvertebrate communities to thermal regime in small Mediterranean streams (southern South America): Implications of global warming - Pedreros, Pablo (2020)
The seasonal nature of the stream thermal regime has been recognized as an important factor for the structure of benthic macroinvertebrate communities. In this study, we show the importance of temperature and the potential implications of global warming on the composition of benthic macroinvertebrate communities in Andean watersheds. Here we show that thermal factors (mean temperature and monthly range) partially explain the seasonal variability of macroinvertebrates in Andean streams. Different thermal requirements were observed for macroinvertebrate families. Optimal monthly mean temperatures estimated for Gripopterygidae (Plecoptera), Hydrobiidae (Gastropoda) and Helicophidae (Trichoptera) were lower than 7 °C, while temperatures for Ameletopsidae, Baetidae (Ephemeroptera), Ecnomidae, Limnephilidae, Hydropsychidae, Leptoceridae (Trichoptera), Elmidae (Coleoptera) and Notonemouridae (Plecoptera) were close to 9.5 °C. According to our estimations, future global warming could cause important changes in the macroinvertebrate composition of Andean watersheds. Gripopterygidae, Austroperlidae, Diamphipnoidae (Plecoptera), Hydrobiidae and Helicophidae (Trichoptera) would be the most vulnerable families under the 2090 temperature predictions due to their preference for low temperature.